6x-9=4x+7

Simple and best practice solution for 6x-9=4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-9=4x+7 equation:


Simplifying
6x + -9 = 4x + 7

Reorder the terms:
-9 + 6x = 4x + 7

Reorder the terms:
-9 + 6x = 7 + 4x

Solving
-9 + 6x = 7 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-9 + 6x + -4x = 7 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-9 + 2x = 7 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + 2x = 7 + 0
-9 + 2x = 7

Add '9' to each side of the equation.
-9 + 9 + 2x = 7 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = 7 + 9
2x = 7 + 9

Combine like terms: 7 + 9 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| x+1/3=-5/9 | | 3/7m=-3/7 | | 5n=0 | | m/-5=-1/3 | | w/-3=-6 | | k-2/5=-67/55 | | d-4=-10 | | 64x^5-64x^3=x^2-1 | | d+10=15 | | 3+a=-5 | | -1/6d=-1/27 | | 64x^5=x^2 | | 18=t+6 | | m/3=6 | | d+1=9 | | t-1/2=23/2 | | b-2=-6 | | a-3/4=-1 | | -8+a=-2 | | -9/4=x-3 | | m/5=-5/6 | | -1/2+w=23/2 | | -1+n=0 | | n/7=5 | | -3/10+t=87/10 | | -1+k=-14/9 | | a+10=15 | | d=3/5 | | d+8=9 | | w+3=-8 | | b+8=65/9 | | a/7=-1/3 |

Equations solver categories